2020
DOI: 10.1002/jac5.1295
|View full text |Cite
|
Sign up to set email alerts
|

Use of continuous glucose monitoring to improve glycemic management: A clinician's guide

Abstract: Adoption of continuous glucose monitoring (CGM) technology in clinical practice has increased over the past few years with numerous studies demonstrating its benefit in persons with diabetes. In addition, the use of CGM systems is now recommended in multiple guidelines for diabetes care. Implementation of personal‐ and professional‐use CGM technology can facilitate patient‐centered discussions in clinical decision making and empower behavioral change. Pharmacists can incorporate CGM into diabetes management pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Peer support from individuals with similar diabetes management routines can help a novice adopt new behaviors or tasks, while advancing their current expertise managing diabetes 23,25,26 . Several studies demonstrated the benefits of the SMA model on clinical outcomes including A1C, cholesterol levels, weight, and adherence to medications 27‐31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peer support from individuals with similar diabetes management routines can help a novice adopt new behaviors or tasks, while advancing their current expertise managing diabetes 23,25,26 . Several studies demonstrated the benefits of the SMA model on clinical outcomes including A1C, cholesterol levels, weight, and adherence to medications 27‐31 …”
Section: Discussionmentioning
confidence: 99%
“…The average reimbursement for CPT 95250 and 952 ranges from $189 to $400 per person. This can also be billed concurrently with DSMES 31 …”
Section: Discussionmentioning
confidence: 99%
“…1,3,7 Several studies demonstrate that pharmacist CGM integration resulted in improvement in clinical outcomes. [8][9][10][11][12] These clinical improvements include improved patient self-efficacy in managing diabetes and A1C reduction. Other studies detail the role of the pharmacist as part of the multidisciplinary team in managing insulin pumps during routine clinical care as well as transitions of care which may include activities such as policy development, patient monitoring, and postdischarge education.…”
Section: Evidence Of Pharmacist Involvement With Diabetes Technologymentioning
confidence: 99%
“…The use of professional CGM can also be beneficial in identifying and correcting patterns of hyperglycemia or hypoglycemia and improving A1c levels in persons with diabetes on non-insulin regimens as well as basal-only insulin regimens. 4 Professional CGM allows the practitioner to make well-informed medication adjustments based on the patient's daily glycemic patterns.…”
Section: Introductionmentioning
confidence: 99%
“…It also serves as an opportunity for persons with diabetes to review their ambulatory glucose profile (AGP) report, associate their glucose patterns with medication‐taking, dietary modifications, and physical activity and experience what it is like to wear a device before considering personal CGM. The use of professional CGM can also be beneficial in identifying and correcting patterns of hyperglycemia or hypoglycemia and improving A1c levels in persons with diabetes on non‐insulin regimens as well as basal‐only insulin regimens 4 . Professional CGM allows the practitioner to make well‐informed medication adjustments based on the patient's daily glycemic patterns.…”
Section: Introductionmentioning
confidence: 99%